Core-shell structure nano calcium carbonate antibacterial composite powder and preparation method thereof
By coating titanium dioxide and nanosilver on the surface of nano calcium carbonate to form a core-shell structure, the problems of large particle sizes and uneven distribution of nanosilver are solved in the existing antibacterial calcium carbonate products, which significantly improves the antibacterial performance and stability.
Patent Information
- Application Number
- CN202411989477.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing antibacterial calcium carbonate products have problems such as large particle size and uneven distribution of nanosilver on the surface of calcium carbonate, which affects the antibacterial performance and application range.
The core-shell structure preparation method is adopted, and a layer of titanium dioxide is first coated on the surface of nano calcium carbonate, and then a layer of nano silver layer to form a core-shell structure antibacterial composite powder of CaCO3@TiO2@Ag.
The uniform distribution of nano silver on the surface of calcium carbonate is achieved, which significantly improves antibacterial performance and stability, and solves the problems of large particle size and uneven distribution.
Smart Images

Figure CN119769506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of calcium carbonate, in particular to a core-shell structured nano calcium carbonate antibacterial composite powder and a preparation method thereof. Technical Background
[0002] Health is a concern for everyone. With the improvement of living standards and the enhancement of health awareness, people pay more and more attention to the hygiene of their work and home environment. In recent years, inorganic nano-antibacterial materials have attracted extensive attention from scientific researchers due to their high stability, broad-spectrum and high-efficiency antibacterial activity, and the fact that they are not prone to produce drug-resistant strains. In terms of disinfection and antibacterial, many inorganic nano-antibacterial materials have been widely used in daily products (such as plastic products and sanitary ware), medical diagnosis, and environmental disinfection and water disinfection. Using inorganic nano-antibacterial materials to inhibit and eliminate harmful microorganisms has become an important means to improve human health. Nanosilver has become an ideal antibacterial material because of its broad-spectrum antibacterial properties, high efficiency, and sustainability. However, nanosilver has problems such as high cost and poor dispersibility that affect performance.
[0003] Calcium carbonate is an important type of inorganic filler, which is widely used in coatings, plastics, rubber, papermaking and other fields. It can significantly improve the processing performance and physical properties of materials and reduce production costs. Calcium carbonate has the advantages of low price, abundant reserves, stable performance, easy processing and non-toxicity. Traditional calcium carbonate products do not have mildew and antibacterial properties. Usually, when producing antibacterial products, it is necessary to add antibacterial materials such as rare earths and nano-precious metals to achieve the antibacterial effect, which limits the application scope of calcium carbonate.
[0004] Studies have shown that using calcium carbonate as a carrier to load nanosilver can not only reduce production costs, improve the dispersibility of nanosilver, but also bring into play the antibacterial properties of nanosilver. For example, patent CN101480194B discloses a method for preparing an antibacterial material based on nano-calcium carbonate. The method prepares an antibacterial material based on nano-calcium carbonate by adding titanium salt or zinc salt, silver salt and phosphate or phosphoric acid, silicate, etc. to a nano-calcium carbonate slurry. The antibacterial material product prepared by the method has high antibacterial properties and high whiteness, solves the problems of low whiteness and high production cost of current domestic inorganic antibacterial agent products, and at the same time improves the added value of nano-calcium carbonate.
[0005] Patent CN109722086A discloses a silver-based antibacterial material containing porous composite calcium carbonate and a preparation method thereof. The inventive method uses ultrafine porous calcium carbonate with a particle size of 0.5-5μm as a matrix, and uses radio frequency induction plasma to prepare nano silver powder and titanium dioxide powder. Then, calcium carbonate, nano silver powder, titanium dioxide powder and other nano metal powders (such as nano copper powder, nano aluminum powder, nano zinc powder, etc.) are added to an organic solvent in proportion and mixed, and then spray dried by a spray dryer to obtain a silver-based antibacterial material containing porous composite calcium carbonate. The antibacterial material has a large specific surface area and a rich pore structure, which can effectively protect the antibacterial component, is conducive to maintaining a long-term effective bactericidal factor concentration, and can release the bactericidal factor over a long period of time, and the bactericidal effect lasts for a long time.
[0006] Patent CN114231053A discloses a method for preparing a needle-like cluster calcium carbonate-silver composite antibacterial material. The method first prepares a needle-like cluster calcium carbonate slurry without adding an inorganic salt as a crystal form controller, then adds a silver ammonia solution prepared from silver nitrate and ammonia water, and reacts for 5 hours to obtain a needle-like cluster calcium carbonate-silver composite antibacterial material. The material has uniform structural dimensions, a needle-like diameter of several hundred nanometers, a length of micrometer level, good compatibility, and can be applied to fields such as papermaking fillers and plastic modification. The product color is adjustable from white to light brown to brown. At the same time, the present invention also gives calcium carbonate antibacterial properties, which can be used in products with antibacterial requirements in industries such as rubber, plastics, papermaking, coatings, and inks, thereby increasing the added value of the product and broadening the application field.
[0007] Although there are many reports on antibacterial materials of calcium carbonate matrix loaded with nano silver, these materials make full use of the advantage of low price of calcium carbonate to reduce cost and expand the application range of calcium carbonate, but most of these antibacterial materials are micron-level and have too large particle size. In addition, these antibacterial materials are only simple mixing of calcium carbonate and nano silver in a specific way, which causes nano silver to be difficult to be evenly distributed on the surface of calcium carbonate, affecting the use effect and application range. Therefore, it is of great significance to study and develop a suitable process technology for preparing calcium carbonate-silver composite powder, realize that nano silver is evenly distributed on the surface of calcium carbonate while the particle size is small, and the development of silver antibacterial materials and calcium carbonate industry is of great significance. Summary of the invention
[0008] In view of the above problems, the present invention proposes a core-shell structured nano calcium carbonate antibacterial composite powder and a preparation method thereof. The method uses nano calcium carbonate as the core, and after coating the surface of calcium carbonate with a layer of titanium dioxide and then a layer of nano silver, forms a CaCO3@TiO2@Ag core-shell structured antibacterial composite powder, which solves the problems of large particle size and uneven distribution of nano silver on the surface of calcium carbonate in existing antibacterial calcium carbonate products. The present invention proposes for the first time a method for preparing a nano calcium carbonate core-shell structured antibacterial composite powder with nano calcium as the core and nano silver as the coating layer, which provides a new research idea for the preparation of silver antibacterial agents and the preparation of calcium carbonate core-shell structures.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder comprises the following steps:
[0011] (1) adding calcium carbonate to an ethanol-water mixture, adding butyl titanate ethanol solution under stirring, and reacting to obtain a CaCO3@TiO2 suspension;
[0012] (2) filtering and drying the suspension obtained in step (1) to obtain CaCO3@TiO2 core-shell structure powder;
[0013] (3) re-dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (2) into anhydrous ethanol, adding 3-isocyanatepropyltrimethoxysilane, stirring in a water bath, filtering and drying;
[0014] (4) dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (3) in deionized water, then adding silver nitrate, and adding a reducing agent sodium citrate solution under stirring at a certain temperature to obtain a CaCO3@TiO2@Ag core-shell structure slurry;
[0015] (5) removing moisture from the CaCO3@TiO2@Ag core-shell structure slurry obtained in step (4) to obtain a CaCO3@TiO2@Ag core-shell structure, i.e., a core-shell structured nano calcium carbonate antibacterial composite powder.
[0016] Preferably, in step (1), in terms of weight ratio, calcium carbonate is 10 parts, with a particle size of 80-150 nm, the ethanol-water mixture is composed of 50 parts of anhydrous ethanol and 10 parts of deionized water, and the butyl titanate ethanol solution is composed of 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol.
[0017] Preferably, in step (1), the stirring rate is 250 r / min, the reaction temperature is 40° C., and the reaction time is 30 min.
[0018] Preferably, in step (3), the amount of anhydrous ethanol used is 80 parts, and the amount of 3-isocyanatepropyltrimethoxysilane used is 10% of the amount of butyl titanate used.
[0019] Preferably, in step (4), the amount of silver nitrate added is 0.39-1.56 parts by weight, and the sodium citrate solution is prepared by mixing 1.95-7.8 parts of sodium citrate with 60 parts of deionized water.
[0020] Preferably, in step (4), the dropping rate of the reducing agent sodium citrate is 0.5-5 mL / min.
[0021] Preferably, in step (4), the stirring speed is 150-550 r / min.
[0022] Preferably, in step (4), the reaction temperature is 30-90° C. and the reaction time is 30-60 min.
[0023] Preferably, in step (2), step (3) or step (5), the drying method is to dry in a forced air drying oven at a temperature of 105-150° C. for a time of 4-12 hours.
[0024] Compared with the prior art, the present invention has many significant technical advantages, which are specifically reflected in the following aspects:
[0025] (1) In terms of preparation process, the present invention proposes a method for indirectly coating silver on the surface of nano-calcium carbonate. The core of this method is that it innovatively uses TiO2 as a bridge to connect nano-calcium carbonate and silver particles, thereby achieving a stable combination between the two. Specifically, firstly, a layer of TiO2 is uniformly coated on the surface of nano-calcium carbonate through specific technical means to form a unique CaCO3@TiO2 core-shell structure. This step not only enhances the stability of nano-calcium carbonate, but also provides a solid foundation for its subsequent combination with silver particles. Subsequently, the silver particles are accurately loaded onto the surface of CaCO3@TiO2 by utilizing the physical phenomenon of electrostatic action, further forming a CaCO3@TiO2@Ag core-shell structure antibacterial composite material product. This innovative preparation process effectively solves the key problems of the current antibacterial calcium carbonate products on the market, such as excessively large particle size and uneven distribution of nano-silver on the surface of calcium carbonate, thereby significantly improving the antibacterial performance and stability of the product.
[0026] (2) From a more macroscopic perspective, the preparation method of the nano-silver coated nano-calcium carbonate core-shell structure proposed in the present invention has not only achieved significant progress and breakthroughs in technology, but also opened up a new path for the preparation of silver antibacterial agents and calcium carbonate core-shell structures. This innovative preparation method not only broadens the research field of related materials, but also provides more possibilities and options for subsequent material development and application. At the same time, in terms of material properties, the CaCO3@TiO2@Ag core-shell structure antibacterial composite material product prepared by the present invention exhibits excellent antibacterial properties, stability and biocompatibility, providing a new solution for the application of materials in related fields.
[0027] (3) In terms of production cost, the preparation method of the present invention has the advantages of simple process, convenient operation, and easy availability of raw materials, which is expected to significantly reduce production costs and improve production efficiency. In terms of industrial application, this innovative achievement has shown great potential and value, injecting new vitality into the upgrading and development of related industries.
[0028] In summary, the invention not only provides a new idea and method for the combination of nano-calcium carbonate and silver particles, but also has a far-reaching impact and positive driving effect on the scientific and technological progress and industrial development in related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of nano calcium carbonate powder with a particle size of 80-150nm in Comparative Example 1;
[0030] Figure 2 This is a scanning electron microscope image of the CaCO3@TiO2 core-shell structure composite powder prepared in Comparative Example 2;
[0031] Figure 3 is a scanning electron microscope image of the CaCO3@TiO2@Ag core-shell structure antibacterial composite powder prepared in Example 1;
[0032] Figure 4 This is a scanning electron microscope image of the CaCO3@TiO2@Ag core-shell structure antibacterial composite powder prepared in Example 2;
[0033] Figure 5 is a scanning electron microscope image of the CaCO3@TiO2@Ag core-shell structure antibacterial composite powder prepared in Example 3;
[0034] Figure 6 is a scanning electron microscope image of the CaCO3@TiO2@Ag core-shell structure antibacterial composite powder prepared in Example 4;
[0035] Figure 7It is the X-ray diffraction spectra of CaCO3, CaCO3@TiO2, and CaCO3@TiO2@Ag core-shell structures;
[0036] Figure 8 The transmission electron microscope image and EDS element distribution image of the CaCO3@TiO2@Ag core-shell structure antibacterial composite powder prepared in Example 4; DETAILED DESCRIPTION
[0037] In order to better present the present invention, it is illustrated by specific implementation cases, which belong to the protection scope of the present invention but do not limit the protection scope of the present invention.
[0038] In an embodiment of the present invention, the method for preparing the core-shell structured nano calcium carbonate antibacterial composite powder comprises the following steps:
[0039] (1) adding calcium carbonate to an ethanol-water mixture, adding butyl titanate ethanol solution under stirring, and reacting to obtain a CaCO3@TiO2 suspension;
[0040] (2) filtering and drying the suspension obtained in step (1) to obtain CaCO3@TiO2 core-shell structure powder;
[0041] (3) The CaCO3@TiO2 core-shell structure powder obtained in step (2) was redispersed in anhydrous ethanol, and 3-isocyanatepropyltrimethoxysilane was added, and the mixture was stirred in a water bath at 80° C. for 2 h, then filtered and dried;
[0042] (4) dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (3) in deionized water, then adding silver nitrate, and adding a reducing agent sodium citrate solution under stirring at a certain temperature to obtain a CaCO3@TiO2@Ag core-shell structure slurry;
[0043] (5) removing moisture from the CaCO3@TiO2@Ag core-shell structure slurry obtained in step (4) to obtain a CaCO3@TiO2@Ag core-shell structure, i.e., a core-shell structured nano calcium carbonate antibacterial composite powder.
[0044] In step (1), according to the weight ratio, calcium carbonate is 10 parts, the particle size is 80-150nm, the ethanol-water mixture is composed of 50 parts of anhydrous ethanol and 10 parts of deionized water, and the butyl titanate ethanol solution is composed of 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol.
[0045] In step (1), the stirring rate is 250 r / min, the reaction temperature is 40° C., and the reaction time is 30 min.
[0046] In step (3), the amount of anhydrous ethanol used is 80 parts, and the amount of 3-isocyanatepropyltrimethoxysilane used is 10% of the amount of butyl titanate used.
[0047] In step (4), the amount of silver nitrate added is 0.39-1.56 parts by weight, and the sodium citrate solution is prepared by mixing 1.95-7.8 parts of sodium citrate with 60 parts of deionized water.
[0048] In step (4), the dropping rate of reducing agent sodium citrate is 0.5-5 mL / min.
[0049] In step (4), the stirring speed is 150-550 r / min.
[0050] In step (4), the reaction temperature is 30-90°C and the reaction time is 30-60min.
[0051] In step (2), step (3) or step (5), the drying method is to dry in a forced air drying oven at a temperature of 105-150° C. for a time of 4-12 hours.
[0052] Technical principle of the present invention:
[0053] (I) Principle
[0054] The preparation of the core-shell structured nano calcium carbonate antibacterial composite powder of the present invention is based on a series of carefully designed chemical reactions and physical effects. First, in step (1), calcium carbonate is added to an ethanol-water mixture, and then a butyl titanate ethanol solution is added. Butyl titanate undergoes a hydrolysis condensation reaction under this environment to generate titanium dioxide (TiO2). At this time, the surface of TiO2 is rich in hydroxyl groups, and hydroxyl groups also exist on the surface of calcium carbonate (CaCO3). Dehydration condensation reaction occurs between these hydroxyl groups to form a strong Ca-O-Ti chemical bond, so that TiO2 is tightly coated on the surface of calcium carbonate, thereby successfully constructing a CaCO3@TiO2 core-shell structure.
[0055] Next, in step (3), 3-isocyanatepropyltrimethoxysilane is used to pretreat the CaCO3@TiO2 particles. In the presence of water, the organosilane molecules (O=NC-(CH2)3-Si(OCH3)3) are rapidly hydrolyzed into trihydroxy intermediates ((OCH2)3-Si-OH). These intermediates have a strong tendency to cross-link with each other to form a network structure, and they form a chemical bond Ti-O-Si with TiO2 at the liquid-solid interface. This step not only further enhances the stability of the core-shell structure, but also provides a good foundation for the subsequent loading of silver particles.
[0056] Then, in step (4), the pretreated CaCO3@TiO2 core-shell structure powder is dispersed in deionized water and silver nitrate is added. Due to the electrostatic effect of the previously formed Si-OH, the Ag+ in the solution is adsorbed onto the surface of CaCO3@TiO2. Subsequently, under the action of the reducing agent sodium citrate, the Ag+ is gradually reduced to silver particles, and finally a stable CaCO3@TiO2@Ag core-shell structure antibacterial composite material is obtained.
[0057] The design of this core-shell structure has multiple unexpected technical effects. On the one hand, the coating of TiO2 can improve the stability and photocatalytic performance of calcium carbonate. TiO2 can produce strong oxidizing active species under light, which can effectively decompose organic pollutants and also has certain antibacterial properties. On the other hand, the loading of silver particles further enhances the antibacterial properties of the material. Silver ions have broad-spectrum antibacterial properties and can effectively inhibit the growth of microorganisms such as bacteria and fungi. Through the design of this core-shell structure, the silver particles are stably loaded on the surface of the composite material and are not easy to fall off, thus ensuring a long-term antibacterial effect.
[0058] (II) Necessity and importance of raw material dosage control
[0059] 1. Calcium carbonate dosage
[0060] In the present invention, the amount of calcium carbonate is 10 parts, and the particle size is controlled to be 80-150nm. The selection of this amount and particle size range is carefully considered. An appropriate amount of calcium carbonate is used as a core material to provide basic structural support and certain functionality for the entire composite powder. Controlling the particle size within the range of 80-150nm can ensure that calcium carbonate has a larger specific surface area, which is conducive to the combination with TiO2 and silver particles, and improves the performance of the composite material.
[0061] 2. Composition of ethanol-water mixture
[0062] The ethanol-water mixture is composed of 50 parts of anhydrous ethanol and 10 parts of deionized water. This ratio of the mixture can provide a suitable environment for the dispersion of calcium carbonate and the hydrolysis of butyl titanate. Anhydrous ethanol can reduce the surface tension of the system, promote the dispersion of calcium carbonate, and also help the dissolution and reaction of butyl titanate. The presence of deionized water is conducive to the hydrolysis and condensation reaction of butyl titanate. If the proportion of ethanol or water in the mixture is not appropriate, it may affect the hydrolysis rate and degree of butyl titanate, thereby affecting the coating effect of TiO2.
[0063] 3. Butyl Titanate Dosage
[0064] The butyl titanate ethanol solution is composed of 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol. The appropriate amount of butyl titanate can ensure that enough TiO2 is generated during the reaction to coat the calcium carbonate. If the amount of butyl titanate is too small, the calcium carbonate may not be completely coated, affecting the integrity of the core-shell structure; while too much may lead to excessive growth of TiO2, affecting the performance of the composite material.
[0065] 4.3-Isocyanatepropyltrimethoxysilane dosage
[0066] The dosage of 3-isocyanatepropyltrimethoxysilane is 10% of that of butyl titanate. This dosage is chosen to form an appropriate amount of silane layer on the surface of CaCO3@TiO2 particles. The presence of the silane layer can enhance the cross-linking effect between particles and improve the stability of the composite material. At the same time, the silane layer can also provide more active sites for the adsorption of silver ions. If the dosage of silane is too small, an effective cross-linking structure and sufficient active sites may not be formed; if the dosage is too large, it may cause particle agglomeration and affect the performance of the composite material.
[0067] 5. Silver nitrate dosage
[0068] The amount of silver nitrate added is 0.39-1.56 parts. Silver nitrate is the source of silver ions. An appropriate amount of silver nitrate can ensure that sufficient silver particles are loaded on the surface of the composite material to achieve good antibacterial properties. If the amount of silver nitrate is too little, it may not provide enough silver ions, affecting the antibacterial effect; and if the amount is too much, it may lead to excessive growth of silver particles, affecting the performance of the composite material.
[0069] 6. Dosage of sodium citrate
[0070] The sodium citrate solution is prepared by mixing 1.95-7.8 parts of sodium citrate with 60 parts of deionized water. As a reducing agent, the amount of sodium citrate used needs to match the amount of silver nitrate used. An appropriate amount of sodium citrate can gradually reduce silver ions to silver particles while avoiding the agglomeration of silver particles caused by too fast a reduction reaction. If the amount of sodium citrate used is too little, the silver ions may not be completely reduced; and if the amount is too much, the reduction reaction may be too violent, affecting the dispersibility of the silver particles.
[0071] (III) Necessity and importance of process parameter optimization
[0072] 1. Stirring rate
[0073] The stirring rate in step (1) is 250 r / min. An appropriate stirring rate can ensure that calcium carbonate is evenly dispersed in the ethanol-water mixture, and also helps the butyl titanate ethanol solution to fully contact with calcium carbonate, thereby promoting the reaction. If the stirring rate is too low, it may cause uneven dispersion of calcium carbonate and butyl titanate ethanol solution, affecting the rate and degree of the reaction; and if the stirring rate is too high, it may destroy the core-shell structure being formed.
[0074] 2. Reaction temperature and time
[0075] In step (1), the reaction temperature is 40°C and the reaction time is 30 minutes. The selection of this temperature and time is to ensure that the hydrolysis and condensation reaction of butyl titanate can proceed fully without excessively consuming energy and time. If the reaction temperature is too low or the time is too short, the hydrolysis of butyl titanate may be incomplete, affecting the formation and coating effect of TiO2; if the reaction temperature is too high or the time is too long, side reactions may occur, affecting the performance of the composite material.
[0076] In step (4), the reaction temperature is 30-90°C and the reaction time is 30-60 minutes. This temperature and time range is selected to ensure that the silver ions can be fully reduced to silver particles under the action of the reducing agent sodium citrate without destroying the core-shell structure. If the reaction temperature is too low or the time is too short, it may lead to incomplete reduction of silver ions and affect the antibacterial effect; if the reaction temperature is too high or the time is too long, it may lead to excessive growth and agglomeration of silver particles, affecting the performance of the composite material.
[0077] 3. Sodium citrate drop rate
[0078] In step (4), the dropping rate of the reducing agent sodium citrate is 0.5-5 mL / min. Controlling the dropping rate of sodium citrate can ensure that the reduction reaction proceeds smoothly and avoid the reaction being too violent and causing the silver particles to agglomerate. If the dropping rate is too fast, the reduction reaction may be completed instantly, generating a large amount of heat and causing the silver particles to agglomerate; while if the dropping rate is too slow, the reaction time may be prolonged and the production efficiency may be reduced.
[0079] 4. Stirring speed
[0080] The stirring speed in step (4) is 150-550 r / min. An appropriate stirring speed can ensure that the silver ions are evenly distributed in the solution, and also helps to disperse the silver particles and avoid agglomeration. If the stirring speed is too low, it may cause uneven distribution of silver ions and silver particles, affecting the antibacterial effect; while if the stirring speed is too high, it may destroy the silver particles being formed, affecting the performance of the composite material.
[0081] 5. Drying method and time
[0082] In steps (2), (3) and (5), the drying method is to dry in a forced air drying oven at a temperature of 105-150°C for 4-12 hours. This drying condition is selected to ensure that the moisture in the composite material can be fully removed without destroying the core-shell structure. If the drying temperature is too low or the time is too short, the moisture may not be completely removed, affecting the stability of the composite material; if the drying temperature is too high or the time is too long, the performance of the composite material may be reduced.
[0083] In summary, the preparation method of the core-shell structured nano calcium carbonate antibacterial composite powder of the present invention successfully constructs a stable core-shell structured antibacterial composite material by accurately controlling the amount of raw materials and optimizing the process parameters, and the process parameter selection has achieved unexpected technical effects. This material has excellent antibacterial properties and stability, and has broad application prospects in the fields of medical care, food packaging, etc.
[0084] In order to make the disclosure of the present invention more complete, it is described below through more specific embodiments.
[0085] Example 1
[0086] A method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder comprises the following steps:
[0087] (1) adding 10 parts of calcium carbonate with a particle size of 80-150 nm to a mixture of 50 parts of anhydrous ethanol and 10 parts of deionized water by weight, stirring at 250 r / min for 10 min, adding a solution prepared by 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol, and reacting at 40° C. for 30 min to obtain a CaCO3@TiO2 suspension;
[0088] (2) filtering the suspension obtained in step (1), and drying it in a forced air drying oven at 105° C. for 10 h to obtain a CaCO3@TiO2 core-shell structure powder;
[0089] (3) The CaCO3@TiO2 core-shell structure powder obtained in step (2) was redispersed in 80 parts of anhydrous ethanol, and 3-isocyanatepropyltrimethoxysilane in an amount of 10% of the amount of butyl titanate was added, stirred in a water bath at 80°C for 2 hours, filtered, and dried in a forced air drying oven at 120°C for 8 hours;
[0090] (4) dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (3) in 50 parts of deionized water, then adding 0.39 parts of silver nitrate, stirring at 150 r / min for 10 minutes, and then adding a reducing agent solution prepared by 1.95 parts of sodium citrate and 60 parts of deionized water at 0.5 mL / min to obtain a CaCO3@TiO2@Ag core-shell structure slurry;
[0091] (5) The CaCO3@TiO2@Ag core-shell structure slurry obtained in step (4) is dried in a 135°C forced air drying oven for 6 hours to obtain a CaCO3@TiO2@Ag core-shell structure, i.e., a core-shell structured nano calcium carbonate antibacterial composite powder.
[0092] Example 2
[0093] A method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder comprises the following steps:
[0094] (1) adding 10 parts of calcium carbonate with a particle size of 80-150 nm to a mixture of 50 parts of anhydrous ethanol and 10 parts of deionized water by weight, stirring at 250 r / min for 10 min, adding a solution prepared by 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol, and reacting at 40° C. for 30 min to obtain a CaCO3@TiO2 suspension;
[0095] (2) filtering the suspension obtained in step (1) and drying it in a forced air drying oven at 150° C. for 4 h to obtain a CaCO3@TiO2 core-shell structure powder;
[0096] (3) The CaCO3@TiO2 core-shell structure powder obtained in step (2) was redispersed in 80 parts of anhydrous ethanol, and 3-isocyanatepropyltrimethoxysilane in an amount of 10% of the amount of butyl titanate was added, stirred in a water bath at 80°C for 2 hours, filtered, and dried in a forced air drying oven at 110°C for 5 hours;
[0097] (4) dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (3) in 50 parts of deionized water, then adding 0.78 parts of silver nitrate, stirring at 250 r / min for 10 minutes, and then adding a reducing agent solution prepared by 3.9 parts of sodium citrate and 60 parts of deionized water at 1.5 mL / min to obtain a CaCO3@TiO2@Ag core-shell structure slurry;
[0098] (5) The CaCO3@TiO2@Ag core-shell structure slurry obtained in step (4) is dried in a 120° C. forced air drying oven for 6 h to obtain a CaCO3@TiO2@Ag core-shell structure, i.e., a core-shell structured nano calcium carbonate antibacterial composite powder.
[0099] Example 3
[0100] A method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder comprises the following steps:
[0101] (1) adding 10 parts of calcium carbonate with a particle size of 80-150 nm to a mixture of 50 parts of anhydrous ethanol and 10 parts of deionized water by weight, stirring at 250 r / min for 10 min, adding a solution prepared by 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol, and reacting at 40° C. for 30 min to obtain a CaCO3@TiO2 suspension;
[0102] (2) filtering the suspension obtained in step (1) and drying it in a forced air drying oven at 135° C. for 7 h to obtain a CaCO3@TiO2 core-shell structure powder;
[0103] (3) The CaCO3@TiO2 core-shell structure powder obtained in step (2) was redispersed in 80 parts of anhydrous ethanol, and 3-isocyanatepropyltrimethoxysilane in an amount of 10% of the amount of butyl titanate was added, stirred in a water bath at 80°C for 2 hours, filtered, and dried in a forced air drying oven at 125°C for 4 hours;
[0104] (4) dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (3) in 50 parts of deionized water, then adding 1.17 parts of silver nitrate, stirring at 550 r / min for 10 minutes, and then adding a reducing agent solution prepared by 5.58 parts of sodium citrate and 60 parts of deionized water at 5 mL / min to obtain a CaCO3@TiO2@Ag core-shell structure slurry;
[0105] (5) The CaCO3@TiO2@Ag core-shell structure slurry obtained in step (4) is dried in a 135°C forced air drying oven for 6 hours to obtain a CaCO3@TiO2@Ag core-shell structure, i.e., a core-shell structured nano calcium carbonate antibacterial composite powder.
[0106] Example 4
[0107] A method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder comprises the following steps:
[0108] (1) adding 10 parts of calcium carbonate with a particle size of 80-150 nm to a mixture of 50 parts of anhydrous ethanol and 10 parts of deionized water by weight, stirring at 250 r / min for 10 min, adding a solution prepared by 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol, and reacting at 40° C. for 30 min to obtain a CaCO3@TiO2 suspension;
[0109] (2) filtering the suspension obtained in step (1) and drying it in a forced air drying oven at 120° C. for 8 h to obtain a CaCO3@TiO2 core-shell structure powder;
[0110] (3) The CaCO3@TiO2 core-shell structure powder obtained in step (2) was redispersed in 80 parts of anhydrous ethanol, and 3-isocyanatepropyltrimethoxysilane in an amount of 10% of the amount of butyl titanate was added, stirred in a water bath at 80°C for 2 hours, filtered, and dried in a forced air drying oven at 125°C for 6 hours;
[0111] (4) dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (3) in 50 parts of deionized water, then adding 1.56 parts of silver nitrate, stirring at 350 r / min for 10 minutes, and then adding a reducing agent solution prepared by 7.8 parts of sodium citrate and 60 parts of deionized water at 2.5 mL / min to obtain a CaCO3@TiO2@Ag core-shell structure slurry;
[0112] (5) The CaCO3@TiO2@Ag core-shell structure slurry obtained in step (4) is dried in a 105°C forced air drying oven for 12 hours to obtain a CaCO3@TiO2@Ag core-shell structure, i.e., a core-shell structured nano calcium carbonate antibacterial composite powder.
[0113] Comparative Example 1
[0114] Nano calcium carbonate powder with particle size of 80-150nm.
[0115] Comparative Example 2
[0116] A method for preparing CaCO3@TiO2 core-shell structure powder comprises the following steps:
[0117] (1) adding 10 parts of calcium carbonate with a particle size of 80-150 nm to a mixture of 50 parts of anhydrous ethanol and 10 parts of deionized water by weight, stirring at 250 r / min for 10 min, adding a solution prepared by 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol, and reacting at 40° C. for 30 min to obtain a CaCO3@TiO2 suspension;
[0118] (2) The suspension obtained in step (1) was filtered and dried in a 120° C. forced air drying oven for 8 h to obtain a CaCO3@TiO2 core-shell structure powder.
[0119] 1. Product performance test
[0120] The products prepared in Examples 1-4 and Comparative Examples 1-2 were tested using a scanning electron microscope, a transmission electron microscope, and an X-ray diffraction spectrum. The test results are as follows: Figure 1-8 shown.
[0121] Scanning electron microscope images can be used to observe subtle changes in the surface of nano-calcium carbonate before and after coating, as well as the morphological characteristics and distribution patterns of the products obtained under different preparation conditions. Figure 1 It can be seen that the nano calcium carbonate used in the present invention has a particle size of about 80-150nm, a spherical or cubic shape, and a smooth surface. After coating with TiO2, the surface of the nano calcium carbonate changes from smooth to relatively rough, indicating that a layer of TiO2 shell is successfully coated on its surface ( Figure 2 ); Then, nano-silver coating was performed on the basis of the TiO2 intermediate layer, and the surface of nano-calcium carbonate became rougher, indicating that there was a silver coating layer on the surface of calcium carbonate. Figure 8 The energy dispersive X-ray spectroscopy (EDS) element distribution diagram further confirmed that the surface of nano-calcium carbonate was uniformly coated with TiO2 layer and nano-silver layer, and a tight and orderly multi-shell core-shell structure was formed between the three. It is worth noting that although SEM and EDS revealed the existence of TiO2 layer, the subsequent X-ray diffraction (XRD) test results only showed the diffraction peaks of calcium carbonate and silver, indicating that the coated TiO2 layer was in an amorphous state. This feature may give the material specific surface properties and reactivity. Figure 3-6 It can also be seen that with the gradual increase in the amount of silver nitrate added to the reaction system, the surface of the nano-calcium carbonate becomes rougher, indicating that the number of nano-silver particles distributed on the surface of the nano-calcium carbonate increases, and the nano-silver coating becomes more uniform; in addition, whether before or after coating, the morphology of the nano-calcium carbonate does not change, and maintains a spherical or cubic morphology.
[0122] 2. Product application effect test experiment
[0123] According to the formula in Table 1, epoxy resin is mixed with curing agent, leveling agent, etc. in proportion, then the product prepared in the embodiment or comparative example is added, and after being fully mixed, it is added to a twin-screw extruder, the feed temperature is adjusted to 75°C, the melting section and the discharge temperature are adjusted to 100°C, and high-temperature melt extrusion is performed. The extruded resin is crushed into powder by a grinder, and the final sample powder coating is obtained by passing through a 160-mesh fine sieve. The powder coating is sprayed on a 50mm×50mm×3mm tinplate with an electrostatic spray gun, and cured at 200°C for 20 minutes to prepare a test sample. According to GB / T 21866-2008 standard, antibacterial tests are performed on Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus), and the results are shown in Table 2.
[0124] Table 1 Basic coating formula
[0125] raw material Recipe 1 Recipe 2 Saturated polyester 15.5% 15.5% Epoxy resin 31.0% 31.0% Curing agent 10% 10% Benzoin 0.5% 0.5% Brightener 0.5% 0.5% Defoaming agent 0.5% 0.5% Leveling agent 1.3% 1.3% Light calcium carbonate 40.7% 30.7% Products prepared in Examples or Comparative Examples 0% 10%
[0126] Table 2 Antibacterial rate test report
[0127]
[0128]
[0129] It can be seen from the test results of Table 2 that, under the same initial bacterial solution concentration, the bacterial concentration of the samples prepared by the embodiments or comparative examples after 24 hours decreased to varying degrees, and the samples with CaCO3@TiO2@Ag core-shell structure particles decreased significantly. Under the same test conditions, the antibacterial rates of the samples added with nano-calcium carbonate against Escherichia coli and Staphylococcus aureus were 21.21% and 19.32%, respectively, which indicates that nano-calcium carbonate has a certain antibacterial effect on Escherichia coli and Staphylococcus aureus, but not obvious. After a layer of TiO2 was coated on the surface of nano-calcium carbonate, the antibacterial rates of the samples against Escherichia coli and Staphylococcus aureus increased to 56.12% and 53.41%, respectively, indicating that TiO2 has a good antibacterial effect, but due to the generation of amorphous TiO2, its antibacterial effect is limited. The samples with CaCO3@TiO2@Ag core-shell structure particles added, under the synergistic effect of TiO2 and nano-silver, further improved the antibacterial rate of the samples against Escherichia coli and Staphylococcus aureus. The antibacterial rate of the samples changed significantly with the different nano-silver content, showing that the more nano-silver was coated, the higher the antibacterial rate of the sample. When the coating amount of nano-silver reached 7.5% (the amount of silver nitrate used was 1.17 parts by weight), the antibacterial rates of the samples against Escherichia coli and Staphylococcus aureus were 99.97% and 99.90%, respectively, meeting the standard of Class I antibacterial performance in GB / T21866-2008.
[0130] From the above test results, it can be seen that the CaCO3@TiO2@Ag antibacterial composite powder prepared by the method of the present invention has a regular morphology, good dispersibility, good coating effect, and exhibits excellent antibacterial properties in the antibacterial tests on Escherichia coli and Staphylococcus aureus. The present invention provides a new preparation method for the preparation of nano-silver antibacterial agents and calcium carbonate core-shell structures, and also injects new vitality into the scientific and technological progress and industrial development in related fields.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder, characterized in that: The method comprises adding butyl titanate solution to an ethanol-water mixed solution of calcium carbonate to obtain CaCO3@TiO2 powder, then heating the CaCO3@TiO2 powder and 3-isocyanate propyltrimethoxysilane with an ethanol solution, and finally reducing silver nitrate with sodium citrate to obtain a CaCO3@TiO2@Ag core-shell structure antibacterial composite powder. The specific process steps are as follows: (1) adding calcium carbonate to an ethanol-water mixture, adding butyl titanate ethanol solution under stirring, and reacting to obtain a CaCO3@TiO2 suspension; (2) filtering and drying the suspension obtained in step (1) to obtain CaCO3@TiO2 core-shell structure powder; (3) re-dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (2) into anhydrous ethanol, adding 3-isocyanatepropyltrimethoxysilane, stirring in a water bath, filtering and drying; (4) dispersing the CaCO3@TiO2 core-shell structure powder obtained in step (3) in deionized water, then adding silver nitrate, and adding a reducing agent sodium citrate solution under stirring at a certain temperature to obtain a CaCO3@TiO2@Ag core-shell structure slurry; (5) removing moisture from the CaCO3@TiO2@Ag core-shell structure slurry obtained in step (4) to obtain a CaCO3@TiO2@Ag core-shell structure, i.e., a core-shell structured nano calcium carbonate antibacterial composite powder.
2. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (1), according to the weight ratio, calcium carbonate is 10 parts, the particle size is 80-150nm, the ethanol-water mixture is composed of 50 parts of anhydrous ethanol and 10 parts of deionized water, and the butyl titanate ethanol solution is composed of 4.2 parts of butyl titanate and 30 parts of anhydrous ethanol.
3. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (1), the stirring rate is 250 r / min, the reaction temperature is 40° C., and the reaction time is 30 min.
4. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (3), the amount of anhydrous ethanol used is 80 parts, and the amount of 3-isocyanatepropyltrimethoxysilane used is 10% of the amount of butyl titanate used.
5. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (4), the amount of silver nitrate added is 0.39-1.56 parts by weight, and the sodium citrate solution is prepared by mixing 1.95-7.8 parts of sodium citrate with 60 parts of deionized water.
6. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (4), the dropping rate of reducing agent sodium citrate is 0.5-5 mL / min.
7. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (4), the stirring speed is 150-550 r / min.
8. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (4), the reaction temperature is 30-90°C and the reaction time is 30-60min.
9. The method for preparing a core-shell structured nano calcium carbonate antibacterial composite powder according to claim 1, characterized in that: In step (2), step (3) or step (5), the drying method is to dry in a forced air drying oven at a temperature of 105-150° C. for a time of 6-12 hours.
10. A core-shell structured nano calcium carbonate antibacterial composite powder prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Calcium carbonate composite bactericidal agent and preparation method thereof
CN101361490A
Method for preparing antimicrobial material using nano calcium carbonate as substrate
CN101480194A
Nano calcium carbonate catalyst wrapped by Ag-loaded titanium dioxide nanoparticles, as well as preparation method and application of nano calcium carbonate catalyst
CN105107537A
Antimicrobial nano titanium dioxide-silicon dioxide aqueous dispersoid of core-shell structure
CN108077308A
Silver-based antibacterial material containing porous composite calcium carbonate and preparation method of antibacterial material
CN109722086A
Cited By
Antibacterial plastic packaging tube and preparation method thereof
CN120716278A
Antibacterial plastic packaging tube and method for manufacturing the same
CN120716278B